A preliminary nuclear magnetic resonance metabolomics study identifies metabolites that could serve as diagnostic markers of major depressive disorder - Mohammed Badamasi, Ibrahim; Maulidiani, Maulidiani; Munn, Sann Lye; Ibrahim, Normala; Shaari, Khozirah; Stanslas, Johnson (Bentham Science Publishers, 2022)
Background: The evaluation of metabolites that are directly involved in the physiological process, few steps short of phenotypical manifestation, remains vital for unravelling the biological moieties involved in the development of the (MDD) and in predicting its treatment outcome. Methodology: Eight (8) urine and serum samples each obtained from consenting healthy controls (HC), twenty-five (25) urine and serum samples each from first episode treatment naïve MDD (TNMDD) patients, and twenty (22) urine and serum samples each s from treatment naïve MDD patients 2 weeks after SSRI treatment (TWMDD) were analysed for metabolites using proton nuclear magnetic resonance (1HNMR) spectroscopy. The evaluation of patients’ samples was carried out using Partial Least Squares Discriminant Analysis (PLS-DA) and Orthogonal Partial Least Square- Discriminant Analysis (OPLSDA) models.